Layout optimization and manning ratio improvement - Yeong, Weng Harn (2010)
The objective of this study is to design a new layout for space optimization and improve manning ratio . An ergonomic new peripheral for IC bonding machine s is also designed to obtain space savings. The study is limited to the IC bonding process of one product on a single production floor of the factory with sampling done on one module containing two rows of machines. The study is divided into 3 major components which is layout optimization, manning ratio improvement and new peripheral design. Layout and peripheral design is mostly don e using AUTOCAD and work sampling methods is used widely in data collection of manning ratio. Data validation is done by surveying production floor workers on their feedback during the ‘trial -run’ of the new layout, manning ratio and peripheral design. A semiconductor manufacturer is selected for this case study. Upon completion of this study, additional machines can be fitted into existing space, manning ratio is improved requiring less manpower for more machines and a new peripheral which is space saving and ergonomic is designed. As a result, there is significant cost savings and improved productivity. Finally, the machine capacity gap to meet customer demand is closed.